Dismantling the Binaries in Ray Bradbury's Fahrenheit 451 (1953) - Hayya Syahrur Romadhon (Universitas Negeri Surabaya, 2025)
The researcher discussed two problems that exist in Fahrenheit 451 novel by pointing out the binary opposition and dismantling them. The Object that was used for this research is Novel by Ray Bradbury titled “Fahrenheit 451”. The narrative revolves around its main character namely Montag and other major characters in facing problems of their world. The method that was used is Jaques Derrida’s binary oppositions and deconstruction theory. Derrida was critical to structuralist approach in dismembering literature works that he stated if they were consist of Binary Opposition. As he stated with his deconstruction method, meaning in text was not universal as it forms resemblance of hierarchy structure which he called Binary Opposition. In Derrida’s concept of Binary Opposition, by analyzing the privileges of Dominant Meaning, the disadvantages of Subordinate Meaning and the instability between paired terms can deconstruct the Binary Oppositions that present in the book. Thus, new interpretation of meanings can give true meaning of being arbitrary. The results in finding Binary Opposition in Novel Fahrenheit 451 are the followings: Independent Woman vs Housewife, Expelled Educated Group vs Uneducated Citizen, Collective Issues vs Individual’s Problems, Job vs Avocation, Taught vs Self-taught, Pleasure vs Pain. Turns out, the researcher is able to dismantle it by reversing the subordinate terms and displacing binary opposition. As a conclusion, Deconstruction theory seeks to disprove commonly accepted notions and present alternatives that may appear contradictory to some. Different points of view may be ignored, despite the fact that truth is commonly taken for granted, suggesting the truth can be subjective.